Postoperative Contralateral Facet Cyst after Endoscopic Unilateral Laminectomy for Bilateral Decompression: A Case Report - WeonMin Cho; Jae Won Shin; Si Young Park; Hak Sun Kim; Seong Hwan Moon (Journal of Orthopaedic Case Reports)
Introduction: Endoscopic unilateral laminectomy for bilateral decompression (Endo-ULBD) is a minimally invasive, motion-preserving surgical technique designed to decompress neural elements while preserving the posterior spinal structures. Because it maintains spinal integrity, the risk of postoperative instability is generally lower than that of conventional decompression techniques. However, microinstability-related complications, such as facet cyst formation, can still occur and may lead to recurrent symptoms. Case Report: A 63-year-old male underwent ULBD for L4–5 lumbar stenosis and showed notable symptom improvement, which enabled his discharge without complications. However, on postoperative day 5, he developed low back pain and right-sided radiating leg pain. At the 3-month follow-up, these symptoms persisted, prompting an MRI, which revealed a right-sided facet cyst formation. Conservative management, including analgesics, was initiated. By the 4-month follow-up, the patient reported significant symptom improvement. Conclusion: This case highlights that despite the minimally invasive nature of Endo-ULBD and its intent to reduce instability, complications related to microinstability, such as facet cyst formation, can still occur. Awareness of such potential complications is crucial for early diagnosis and management.